Proton migration in bulk orthorhombic barium cerate using density functional theory - Jeong, Yong-Chan; Kim, Byung-Kook; Kim, Yeong-Cheol (ELSEVIER, 2014)
Proton migration in bulk orthorhombic barium cerate was investigated with consideration of effects of yttrium dopant and proton interaction using density functional theory. A proton attached to an oxygen ion migrates via a combination of rotation around the oxygen ion and transfer to a neighboring oxygen ion. Types of proton transfers are divided into the intra-octahedral proton transfer in a cerium-octahedron and the inter-octahedral proton transfer between two neighboring cerium-octahedrons. The energy barrier for the intra-octahedral proton transfer increases significantly when an yttrium ion is substituted for a cerium ion, while the inter-octahedral proton transfer showed less increase in the energy barrier due to a short distance for proton transfer. As a result, along the pathway for proton migration via the inter-octahedral proton transfer, the energy barrier for proton rotation is the highest. However, this value is lower than that of the experimentally measured energy barriers. When the two protons are incorporated in yttrium-doped barium cerate, the proton rotation shows an increase of energy barrier due to the proton interaction, resulting in good agreement with the experimentally measured ones. (C) 2014 Elsevier BY. All rights reserved.
Keywords: TOTAL-ENERGY CALCULATIONS; ELECTRICAL-CONDUCTIVITY; MOLECULAR-DYNAMICS; ZIRCONATE; MOBILITY; HYDROGEN; BACEO3